The Self Possessed: Deity and Spirit Possession in South Asian Literature and Civilization, Frederick M. Smith - Mayer, Robert (Buddhist Studies Review, 2007)
The Self Possessed: Deity and Spirit Possession in South Asian Literature and Civilization, Frederick M. Smith (New York: Columbia University Press, 2006), 13 illus., pp. xxvii+701, $60.00/£35 (cloth), ISBN: 0-231-13748-6